Feasibility Study of the Upton Scott House for Mrs. Coleman duPont - Cosans, Betty (My University, 1972)
The purpose of this feasibility study was to determine if the Scott house site warranted full-scale investigation and, if so, to formulate a series of recommendations to that end. This preliminary study involved three phases: 1. Construction of an historical base map illustrating the chronological sequence of ownership, development, and change. 2. Construction of an archaeological base map recording all standing structures and visible features. 3. Limited test excavations, the results of which were incorporated into the archaeological base map. Work was carried out by a site supervisor and two crew members during the week of July 31-August 4, 1972.
Keywords: 18AP18